Influence of Organizational Trust and Organizational Empowerment on Employee Job Involvement at a Multinational Organization in Ghana - Nkrumah, N.Y.A. (University of Ghana, 2013)
The purpose of the current study was to examine the relationship between organizational trust and organizational empowerment on employee job involvement. A random sample of 192 workers from the Nestle Ghana Limited participated in the survey. The moderating effect on the relationship between organizational trust and organizational empowerment on employee job involvement was also examined. It was hypothesised that, the presence of organizational trust and organizational empowerment would cause employees to reciprocate with job involvement and also the presence of perceived job insecurity of employees will impact the strength of the relationships between trust and empowerment on employee job involvement. Hierarchical regression and moderation analysis were run on the data. Results indicated a positive relationship between organizational trust and job involvement. Organizational empowerment also had a positive relationship with employee job involvement, with job insecurity moderating this relationship as predicted. However job insecurity did not moderate the relationship between organizational trust and job involvement. Within the sub dimensions of empowerment also, fluidity in information sharing was a better predictor of employee job involvement dynamic structural framework and control of work place decisions. Organizational empowerment was a better predictor of employee job involvement than organizational trust. The results are described within the framework of social exchange where the tenets of the theory are clearly seen in the reciprocation of the amount of trust and empowerment given dictating the amount of job involvement to be received. The results of job insecurity moderating in some instances, reflects that the psychological contract theory needs to be reappraised, by identifying and explaining the exceptions that exist with contract violations and subsequent withdrawal of services.
Thesis (MPhil) - University of Ghana, 2013